(untitled) - Hannan, Ed. (Hoboken, N.J., 2006)
The revised field companion for construction, recreation department, and landscape professionals Put it in your pocket and go! For the busy professional working on-site--this updated, handy pocket reference puts all the formulas and calculations you need at your fingertips.
Keywords: Building sites,Civil engineering,Engineering mathematics,Xây dựng các trang web,Xây dựng dân dụng,Kỹ thuật toán học; Design,Mathematics,Mathematics,Formulae,Thiết kế,Toán học,Toán học,Công thức